Array - Winisudo, Ridho Tri; Jacky, M. (Paradigma, 2023)
KH. Ali Mas’ud became the most influential figure in Islamic learning until he died. KH. Ali Mas’ud has become one of the scholars from Sidoarjo who has the same rank as a saint, this makes people who deliberately make pilgrimages to the grave of KH. Ali Mas’ud. The pilgrimage tradition carried out by the pilgrims of the santri community at the tomb of KH. Ali Mas’ud is a form of presence to adapt to what already exists, namely the pilgrimage tradition which provides an imposition that moves the santri pilgrims to live it. This study aims to identify the social facts of pilgrims from the santri community at KH. Ali Mas’ud or known as Mbah Ud Sidoarjo. The method used in this research is qualitative with a phenomenological study approach with Emile Durkheim’s social fact theory as the analytical tool. The results of the study indicate that there are social facts that exist in the pilgrimage of the santri community at KH. Ali Mas’ud. With data findings such as Background, Knowledge, Beliefs, Experiences, Feelings, Pilgrimage goals of the santri community which are analyzed by means of identification (collective, external, and coercive) and types (material and non-material). Keywords: Pilgrims, Social Facts, Beliefs, Tradition, KH. Ali Mas’ud